2021
DOI: 10.3892/etm.2021.10356
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the long noncoding RNA XIST on the inflammatory polarization of microglia in cerebral infarction

Abstract: Proinflammatory polarization of microglia aggravates brain injury in cerebral infarction. The present study focused on the role of long non-coding (lnc)RNA X-inactive specific transcript (XIST) in the phenotype modulation of microglia. It was revealed that lncRNA XIST was significantly upregulated in both a mouse cerebral infarction model induced by middle cerebral artery occlusion (MCAO) and an activated microglial model induced by oxygen/glucose deprivation (OGD). The overexpression of XIST enhanced the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In this review, the lncRNA/circRNA-miRNA-mRNA regulatory network also exists in microglia and astrocyte mediated neurological diseases, including SCI (Figure 1; Shao et al, 2020; FIGURE 1 | The lncRNA/circRNA-miRNA-mRNA regulatory network in microglia and astrocyte regulated neurological diseases. Xu S. et al, 2020;Zhao Q. et al, 2020;Cui et al, 2021;Xiang et al, 2021;Chen et al, 2022), TBI (He et al, 2021;Liu N. et al, 2021;Meng et al, 2021), cerebral IRI (Figure 1; Wang et al, 2020c;Yang et al, 2021), stroke (Figure 1; Qi et al, 2017;Han B. et al, 2018;Tian et al, 2021;Zhang M. et al, 2021), epilepsy (Figure 1; Feng et al, 2020;Han C. L. et al, 2020;Wan and Yang, 2020;Xiaoying et al, 2020), neuropathic pain (Figure 1; Chen M. et al, 2020), PD (Figure 1; Cao et al, 2018Cao et al, , 2021, and depression (Figure 1; . We also found that some therapies can impair the ncRNA-glial cell axis and thus inhibit disease development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this review, the lncRNA/circRNA-miRNA-mRNA regulatory network also exists in microglia and astrocyte mediated neurological diseases, including SCI (Figure 1; Shao et al, 2020; FIGURE 1 | The lncRNA/circRNA-miRNA-mRNA regulatory network in microglia and astrocyte regulated neurological diseases. Xu S. et al, 2020;Zhao Q. et al, 2020;Cui et al, 2021;Xiang et al, 2021;Chen et al, 2022), TBI (He et al, 2021;Liu N. et al, 2021;Meng et al, 2021), cerebral IRI (Figure 1; Wang et al, 2020c;Yang et al, 2021), stroke (Figure 1; Qi et al, 2017;Han B. et al, 2018;Tian et al, 2021;Zhang M. et al, 2021), epilepsy (Figure 1; Feng et al, 2020;Han C. L. et al, 2020;Wan and Yang, 2020;Xiaoying et al, 2020), neuropathic pain (Figure 1; Chen M. et al, 2020), PD (Figure 1; Cao et al, 2018Cao et al, , 2021, and depression (Figure 1; . We also found that some therapies can impair the ncRNA-glial cell axis and thus inhibit disease development.…”
Section: Discussionmentioning
confidence: 99%
“…XIST serves as a sponge for miR-96-5p to antagonize inhibitory effects of miR-96-5p on the TNF-α expression. XIST up-regulation increases TNF-α expression through the miR-96-5p-IKKβ-NF-κB axis (Zhang M. et al, 2021). Moreover, TNF-α stimulation can increase XIST mRNA levels in BV2 cells.…”
Section: Strokementioning
confidence: 96%
See 2 more Smart Citations
“…no. 20141012; Damao Chemical Reagent Factory) at a dose of 300 mg/kg weight (36). After routine disinfection, the following steps were undertaken: i) The skin was cut along the midline of the neck; ii) the muscle and fascia were separated layer by layer; iii) the vagus nerve was separated from the common carotid artery on the right; iv) the external carotid artery was ligated with nylon filament; and v) the middle cerebral artery was blocked by gently introducing 0.26-mm nylon filament (Ruibo Biotechnology Co., Ltd.) through the right common carotid artery.…”
Section: Animalsmentioning
confidence: 99%